(untitled) (Baghdad Science Journal, 2008)
the mixing time is one of the most useful criterions for characterization of the broths mixing intensity and for scaling up of biosynthesis processes. this parameter value depends mainly on the presence of biomass in the broths, mixing system characteristics and operating conditions. For quantifying the influence of these factors on mixing efficiency, this study was carried out for simulated fermentation aerated broths consisted of carboxymethyl cellulose sodium salt (CMCNa) taking into account the broth’s viscosity, rotation speed (rpm) and the stirrer geometry. The experimental results were used in obtaining a correlation to calculate the mixing time for Re <5000, domain of flow regime for which only few data are available from literature. this model offer a good concordance with the experimental results, the average deviation being of 6.6% for CMCNa solutions and can be used for fermentation scaling up.